2002
DOI: 10.1097/00002820-200208000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Risk-factor and Screening Awareness Among Women Nurses and Teachers in Amman, Jordan

Abstract: Breast cancer awareness studies of women in Jordan do not exist. This study used data from 163 nurses and 178 teachers surveyed in Amman to determine 2 dimensions of breast cancer awareness: general breast cancer awareness, defined as knowledge of risk factors associated with the disease and breast cancer screening awareness, defined as knowledge of breast self-examination and mammography. The survey instrument was based on 2 previously validated knowledge-based questionnaires in the literature (Breast Cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
57
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 15 publications
9
57
0
1
Order By: Relevance
“…Results of other studies support our findings: breast cancer risk factors have been reported as never given birth, low fertility rate, late pregnancy, early menstruation, late menopause, history of breast disease, advanced age, physical inactivity and lack of exercise, fat-rich diet, smoking, alcohol intake, family history of breast cancer, obesit, prolonged use of contraceptives, high socioeconomic status and working women (10,11,13,20,21,23,25). Although the level of information of the nurses regarding breast cancer risk factors vary according to studies, Ahmed et al (20) have reported this level among nurses in Karachi from 7 hospitals as 35% good , 40% moderate , and 25% poor.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Results of other studies support our findings: breast cancer risk factors have been reported as never given birth, low fertility rate, late pregnancy, early menstruation, late menopause, history of breast disease, advanced age, physical inactivity and lack of exercise, fat-rich diet, smoking, alcohol intake, family history of breast cancer, obesit, prolonged use of contraceptives, high socioeconomic status and working women (10,11,13,20,21,23,25). Although the level of information of the nurses regarding breast cancer risk factors vary according to studies, Ahmed et al (20) have reported this level among nurses in Karachi from 7 hospitals as 35% good , 40% moderate , and 25% poor.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies regarding knowledge and practices of nurses on breast cancer prevention from Turkey (11)(12)(13)(17)(18)(19) and abroad (10,(20)(21)(22)(23)(24)(25)(26)(27) have showed significant differences in knowledge and application of BSE, CBE and mammography among nurses. These differences are thought to originate from research methodology, nurses' socio -demographic (age, education level, marital status, etc.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies indicate that doctors often do not offer BCS services to women. Other health care providers (HCP) might not have adequate knowledge of BCS and risk factors related to breast cancer in the Middle East, thus limiting their ability to encourage patients to engage in BCS activities (Bener et al, 2001;Haji-Mahmoodi, 2002;Madanat and Merrill, 2002;Dow Meneses and Yarbro, 2007;Alkhasawneh et al, 2009;Jaradeen, 2010;El Hajj and Hamid, 2011). Previous studies in the region indicate low participation rates in breast cancer screening activities among women (Bener et al, 2001;Bener et al, 2002;Azaiza and Cohen, 2008;Bener et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Accurate and varied sources of information about breast health and BCS from health care providers (especially physicians), mass media, and social networks can positively influence women's knowledge and practice of BCS (Al-Qattan, et al, 2007;Dandash and Al-Mohaimeed, 2007;Montazeri, et al, 2008;Hoffman et al, 2010). Facilitators of BCS behavior include having support from male relatives, receiving information about breast cancer or BCS from health care professionals (HCP) other than doctors, and having a doctor's recommendation (Haji-Mahmoodi, 2002;Madanat and Merrill, 2002;Cohen and Azaiza, 2005;Azaiza and Cohen, 2006;Shirazi et al, 2006;Dandash and Al-Mohaimeed, 2007;Dow Meneses and Yarbro, 2007;El Saghir et al, 2007;Alkhasawneh et al, 2009;Gürsoy et al, 2009;Jaradeen, 2010;El Hajj and Hamid, 2011).…”
Section: Introductionmentioning
confidence: 99%